2019
DOI: 10.11114/ijce.v2i2.4393
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Chinese as a Foreign Language Teachers’ Relationship with Their Students in the Australian Context

Abstract: This study explores the transformation of teacher–student relationship between expatriate Chinese as a Foreign Language (CFL) teachers and their students situating in the Australian educational context. The disparity of tradition between the two educational cultures influences substantially on communication between teachers and students within classroom. To better understand how CFL teachers’ background educational culture may impact their interaction with Australian students, focus group discussion data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Although the sample size is limited, this study reveals a new angle to approach existing issues. On the whole, our findings support the existing literature (e.g., Chen, 2015 ; Moloney and Xu, 2015 ; Han et al, 2019 ; Han and Han, 2019 ) that CFL teachers experience various challenges while teaching in foreign contexts, and that their institutional life and teacher identity have to be reorganized according to new social norms. However, instead of examining external factors, such as social environment, pedagogy, and curriculum, we delved into CFL teachers’ internal operation of social interaction and found divergences of self and other in CFL teacher identity development in Australia, which not only includes objective relational process between individuals but also ideological and axiological factors that influence the wholeness of CFL teachers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the sample size is limited, this study reveals a new angle to approach existing issues. On the whole, our findings support the existing literature (e.g., Chen, 2015 ; Moloney and Xu, 2015 ; Han et al, 2019 ; Han and Han, 2019 ) that CFL teachers experience various challenges while teaching in foreign contexts, and that their institutional life and teacher identity have to be reorganized according to new social norms. However, instead of examining external factors, such as social environment, pedagogy, and curriculum, we delved into CFL teachers’ internal operation of social interaction and found divergences of self and other in CFL teacher identity development in Australia, which not only includes objective relational process between individuals but also ideological and axiological factors that influence the wholeness of CFL teachers.…”
Section: Discussionsupporting
confidence: 87%
“…While others report that transferring to another culture has resulted in CFL teachers’ transformation of professional identity from “a sage on the stage” to “a guide by the side” considering to cater students’ needs. However, this transformation did not bring good effects and put CFL teachers in a dilemma and self-questioning ( Han et al, 2019 ). Wang and Du (2014) studied immigrant Chinese teachers’ professional identity transformation in an intercultural context (Danish) and found that the professional identity of Chinese teachers is shaped both by their previous experiences of teacher-student relationship in the Chinese culture and their new experience as teachers in the Danish culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, some studies found that CFL teachers’ identity tended to be authoritarian and teacher-centered under the influence of Confucianism (e.g., Moloney and Xu, 2015 ; Han and Han, 2019 ). On the other hand, others reported that the experience of teaching in another culture resulted in CFL teachers’ transformation of professional identity from an authoritative teacher on stage to a guiding facilitator by side (e.g., Han et al, 2019 ; Han and Ji, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%